Pengembangan Sistem Arsip berbasis Desktop menggunakan Metode Rapid Application Development (Studi Kasus: SMK Muhammadiyah 1 Malang) - Andi Kautsar Thariq; Retno Indah Rokhmawati; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The issues discussed relate to archive management at the Muhammadiyah 1 Malang Vocational School and to the obstacles to archive management. The data is collected by observation and questioning. The purpose of this research is to build an archive management information system at Muhammadiyah 1 Malang Vocational High School so that file management is much easier. The results of this study show that archival management at Muhammadiyah 1 Malang Vocational School works well and smoothly. This is demonstrated by the ability to manage archives, manage filing loans, and print a history of filing loans. Although there are still deficiencies, they can not use this application to create archives in the form of letters, and users wishing to borrow archives must contact the officer for review. Based on the tests performed, the results of functional tests conducted using the Black Box test approach in 17 test cases performed have shown that 100% of the system is valid when tested in certain cases. And for the test results of the User Acceptance Testing (UAT) from the completed questionnaire, the respondents fulfilled the satisfaction of the respondents. This shows that the function of this application matches the functional requirements of the system defined in the design process.